The Discourse of Post-capitalism as a Reflection of the Crisis of Globalization - D. G. Evstafiev (Vestnik MGIMO-Universiteta)
The primary objective of this article is to construct a comprehensive conceptual definition of "post-capitalism." The contemporary global landscape, characterized by postmodernity, is currently undergoing a profound institutional crisis. This crisis impacts both its economic underpinnings, rooted in the dominance of financial capitalism, and its societal foundations, which revolve around a universal model of social development built upon a universalist model of consumption.Discourses surrounding post-capitalism within Russian and Western academic and expert circles exhibit unique characteristics. However, they share common traits. On one hand, these discourses reflect an acknowledgment of the impasses inherent in existing models of globalization. On the other hand, they recognize the transformation of capitalism as a universal socio-economic system that forms the bedrock of international relations. This article underscores the inescapable rise of non-economic factors influencing socio-economic systems' development, including their role in shaping international relations.Post-capitalism is best understood as a collection of principles guiding spatial organization and the establishment of economic and political relationships within these spaces, rather than a specific developmental model. Positioned as an element within the broader return to a spatiality, post-capitalism is predominantly discussed within the context of international processes, serving as a transitional phase in international political and economic relations.